“Metal Detectors”: la tecnologia attuale per la prospezione archeologica - Di Cesare, Renato (Archeomatica, 2022)
The "metal detector" is an instrument that uses some electromagnetic properties of metals to detect the presence of metal objects buried in the ground. Originally developed for military applications, more precisely to clear minefields, metal detectors find use in many other applications: from the detection of weapons on passengers in airports to geological and (with many reserves) archaeological research, or, more simply, to the identification of electrical cables or metal pipes underground or in the walls of buildings.